The Mediating Role of Technological Acceptance in the Relationship between AI Education Platforms and Students’ Learning Outcomes - Ahmed, Rizwan (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This paper is aimed to examine the interrelationship between AI education platforms (AIEP), technological acceptance (TA), and learning outcomes (SLO) of students in the context of Karachi-based private schools in Pakistan. The framework was constructed using the Theory of Planned Behaviour which was used to measure TA. Data was collected in the questionnaire survey format concerned the perceptions of students and teachers on the use of AIEP in their schools. Multiple regression analysis and Sobel test analysis of 150 respondents revealed that TA is the mediating variable between AIEP and SLO. That is, where AIEP positively affect TA, which in turn positively affect SLO, the effect of mediation can be observed. The additional analysis also found out that the two dimensions of TA, perceived usefulness and ease of use were the most significant when it comes to the determination of student engagement and academic success. The conclusion that provides the schooling sector with a refinement of the variables that can contribute to the greater adoption of AI tools by the students. This help schools enhance the quality of education, innovation, and the general learning performance